Radio protective effect of 500/0 watermelon (citrullus lanatus (thunb.) matsum. and nakai) juice in liver / Ruzaana Hanifah - Hanifah, Ruzaana (2015)
Ionizing radiation is one of a radicals sources inside human body which resulted in oxidative damage. Overproduction of ROS and imbalance of antioxidant production can contribute to various pathological condition such as cancer and tissues injuries. To date, lack of information about capability of watermelon in reducing oxidative damage cause by oxidant such as IR. Therefore, the present study was aimed to evaluate the radio protective effect of 50% watermelon (Citrullus lanatus (Thunb.) Matsum. and Nakai) juice against low dose ionizing irradiation - induced oxidative stress in liver. Eighteen healthy male ICR mice was randomly divided into three group consist of negative control group, radiation and treatment groups (n=6). Negative control and radiation groups mice received filtered tap water, but radiation group was exposed to low dose radiation (IOOflGy) on day 15 whereas treatment group was supplemented with 50 % of watermelon juice ad libitum for 14 days prior to total body X-ray exposure in single dose. SODs inhibition activities, total glutathione (GSH) and Malondialdehye (MDA) level was assessed in mice liver. Level of DNA damage was studied by measuring olive tail moment using Comet assay. The SOD inhibition activities and GSH level showed significant reduction in radiation and treatment group compared to negative control group (P < 0.05), however no significant marked between both groups although treatment group had higher mean compared to radiation group. MDA level among all the groups showed no significant differences, but in treatment group showed decrease of MDA level compared to radiation group. However, finding of DNA damage observed significantly increased in radiation group compared to negative control and treatment groups (P < 0.05). In conclusion, present study reveal biological evidence that support radio protection effect of 50% watermelon juice in molecular changes and several biochemical changes against radiation-induced oxidative damage for 14 days in mice liver.